Object-based teaching and learning for a critical assessment of digital technologies in arts and cultural heritage - Hess, Mona; Garside, Daniel; Nelson, T.; Robson, Stuart; Weyrich, Tim (International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences - ISPRS Archives, 2017)
As cultural sector practice becomes increasingly dependent on digital technologies for the production, display, and dissemination of art and material heritage, it is important that those working in the sector understand the basic scientific principles underpinning these technologies and the social, political and economic implications of exploiting them. The understanding of issues in cultural heritage preservation and digital heritage begins in the education of the future stakeholders and the innovative integration of technologies into the curriculum. This paper gives an example of digital technology skills embedded into a module in the interdisciplinary UCL Bachelor of Arts and Sciences, named "Technologies in Arts and Cultural Heritage", at University College London.
CRIS-Team Scopus Importer:2022-07-26
Keywords: 3D recording; Cultural heritage; Digital technologies; Interdisciplinarity; Laser scanning; Learning; Object-based teaching; Photogrammetry